2003
DOI: 10.4049/jimmunol.170.11.5658
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Ligand 5/RANTES Chemokine Antagonists Aggravate Glomerulonephritis Despite Reduction of Glomerular Leukocyte Infiltration

Abstract: The chemokine CC chemokine ligand (CCL)5/RANTES as well as its respective receptor CCR5 mediate leukocyte infiltration during inflammation and are up-regulated early during the course of glomerulonephritis (GN). We tested the effects of the two CCL5/RANTES blocking analogs, Met-RANTES and amino-oxypentane-RANTES, on the course of horse apoferritin (HAF)-induced GN. HAF-injected control mice had proliferative GN with mesangial immune complex deposits of IgG and HAF. Daily i.p. injections of Met-RANTES or amino-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 48 publications
5
91
0
Order By: Relevance
“…An attenuation of neutrophil transmigration, however, is not necessarily protective against I/R injury, because transmigrated neutrophils as well as macrophages are suggested to play an important role during postischemic tissue remodeling and healing. 22,46,47 CD4 ϩ T cell deficiency as well as interruption of the CD40 -CD40L and CD28 -B7-dependent signaling mechanisms have a protective impact not only on hepatocellular but also on microvascular hepatic I/R injury. The postischemic breakdown of sinusoidal perfusion is considered a key factor in the pathogenesis of microvascular I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…An attenuation of neutrophil transmigration, however, is not necessarily protective against I/R injury, because transmigrated neutrophils as well as macrophages are suggested to play an important role during postischemic tissue remodeling and healing. 22,46,47 CD4 ϩ T cell deficiency as well as interruption of the CD40 -CD40L and CD28 -B7-dependent signaling mechanisms have a protective impact not only on hepatocellular but also on microvascular hepatic I/R injury. The postischemic breakdown of sinusoidal perfusion is considered a key factor in the pathogenesis of microvascular I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many temporal studies in both immune and non-immune-initiated models of kidney disease have shown a clear association between macrophage accumulation and the development of renal injury (reviewed by Nikolic-Paterson et al [2]). However, not all studies have found concordance between increased macrophage numbers and more severe renal injury (6,7), suggesting that there may be significant functional heterogeneity within the infiltrating macrophage population. Indeed, macrophages can perform many different functions according to the local microenvironment in which they are present, ranging from a pro-inflammatory response to microbial infection to the removal of apoptotic cells, downregulation of the innate/immune response, and tissue repair.…”
mentioning
confidence: 99%
“…AOP-RAN-TES reduced macrophage infiltration in Thy1.1 antibody-induced glomerulonephritis in rats (11), and Met-RANTES improved rat renal allograft rejection (12). However, both antagonists aggravated immune complex glomerulonephritis in mice, which was associated with antagonist-induced modulation of macrophage function toward a proinflammatory phenotype (13).…”
mentioning
confidence: 99%